Efektifitas Model Pembelajaran Drill disertai Media Pembelajaran Crossword Puzzle Terhadap Aktivitas dan Hasil Belajar Siswa pada Mata Pelajaran TIK Kelas VII SMPN 12 Semarang - Ardiyanti, Yunita Nur Ayu; Ananta, Henry; Utomo, Aryo Baskoro (Jurusan Teknik Elektro Universitas Negeri Semarang, 2016)
This study aims to determine students' learning activities and improving student learning outcomes in subjects ICT class VII High School 12 Semarang after using drill method learning with instructional media crossword puzzle. The design used in this study is nonequivalent control group design. The tools used in this study was the observation sheet and test sheet pretest and posttest. From the analysis of the data, the result of observation of student learning activities as a whole in the experimental class earned an average percentage of 83%, this data shows the experimental class students learning activities is high. On average value of pretest and posttest cognitive learning outcomes in the experimental class at 62.56 and 79.22. While the average value of pretest and posttest in control class is 62.73 and 73.83. To increase students' cognitive learning outcomes seen from the gain test. The result of the gain in the experimental class of cognitive learning outcome category was 0.44. While the test results on the gain control class 0.29 low category. Based on the research results can be concluded that the use of learning model drill with instructional media crossword puzzle on the activity and student learning outcomes in subjects ICT class VII High School 12 Semarang more effective than expository teaching model with the lecture method.